Disparrhopalites naasaveqw n. sp. from caves at Wupatki National Monument, Arizona, synonymy of Dietersminthurus Palacios-Vargas, Cuéllar & Vázquez, 1998 with Disparrhopalites Stach, 1956 and composition of Songhaicinae (Collembola: Sminthuridae) - Bernard, Ernest C.; Wynne, J. Judson (Zootaxa, 2017)
Disparrhopalites naasaveqw n. sp. is described from a cave at Wupatki National Monument, Arizona. It differs from D. patrizii (Cassagnau & Delamare Deboutteville, 1953) in having pigment and a well-developed ungual cavity, and from D. tergestinus Fanciulli, Colla & Dallai, 2005 by having pigment, 8+8 eyes and a well-developed ungual tunica. Dietersminthurus enkerlinius Palacios-Vargas, Cuéllar & Vázquez, 1998 is transferred to Disparrhopalites Stach, 1956 as D. enkerlinius (Palacios-Vargas, Cuéllar & Vázquez, 1998) n. comb. The sminthurid subfamily Songhaicinae Sánchez-García & Engel, 2016 (type genus Songhaica Lasebikan, Betsch & Dallai, 1980) is redefined and the genera Disparrhopalites, Gisinurus Dallai, 1970, Soqotrasminthurus Bretfeld, 2005 and Varelasminthurus Da Silva, Palacios-Vargas & Bellini, 2015 are transferred to this subfamily. A key is provided for separation of included genera. Effects of climate change on presumed cases of cave restriction in the American Southwest are discussed.